Layer-to-layer distance determines the performance of 3D bio-electrochemical lamellar anodes in microbial energy transduction processes - Massazza, Diego Ariel (2018)
Microbial fuel cells (MFCs) harness the metabolic machinery of electro-active bacteria to transfer electrons from organic molecules to polarized anodes. In this context, increasingly higher anode surface areas have been pursued for maximizing MFC performance. In this study we prepared 3D layered Ti4O7 electrodes with different interlayer spacings (from 10 to 100 μm) but maintaining the same total void fraction (90%), so as to modify the electrode surface-to-volume ratios. This allowed us to test the hypothesis that there must be a limit in surface area per unit volume restricting the efficiency of 3D porous bio-electrochemical anodes. The lamellar scaffolds were evaluated in three-electrode cells cultured with G. sulfurreducens. Regardless of the electrode interlayer spacing or the biofilm developmental stage, the electron transfer rate was constant (0.11 pA per bacterium), with current scaling linearly with the size of the microbial population. However, maximum volumetric current densities (20 ± 0.8 kA m-3) were not obtained from electrodes with maximum surface-to-volume ratios (shorter interlayer distances), because bacterial biomass was not directly proportional to the surface area. This demonstrated that, by controlling the spacing between layers, it is possible to modulate the amount of bacteria per electrode unit volume, this ratio determining the final electrode performance. The limit obtained in surface area suggested that other effects, such as fluid dynamic constraints inside the "slit-shaped" pores, must be playing a critical role in anode performance.